Protective Effects of Methionine on some Physiological and Biochemical Parameters of Triton-Stressed Male Rats - Zaid S. M. A-Ani (Pakistan Journal of Medical & Health Sciences, 2023)
The aim of this study is to find out the effect of amino acid methionine 35 mg/kg of feed with the diet to minimize the harms caused by oxidative stress resulting from treatment with Triton at a dose of (300 ml/kg) on physiological and biochemical parameters. This study was conducted at the Technical Institute/Mosul for the period 1/12/2021 - 1/2/2022 to find out the protective effects of the amino acid methionine on some physiological and biochemical parameters of Triton-stressed white male laboratory rats, as their weight ranged from 180-220 g and their ages ranged between 12- 14 weeks. After confirming that they are free of diseases, with the help of a veterinarian. Some biochemical parameters were measured, namely, glucose, cholesterol T.C., triglycerides T.G, (LDL-c) low-density lipoprotein cholesterol, (VLDL-c) very low-density lipoprotein cholesterol, (HDL-c) high-density lipoprotein cholesterol, and the atherogenic index. In this study, were used 24 white male rats, distributed randomly into four groups of 6 rats/group. And it was as follows: Control group: was injected a 1 ml of distilled water to equalize the stress of holding the rats. Triton group: They were injected with Triton 300 ml/kg body weight of Triton. Methionine group: was given (35 mg/kg diet) of the amino acid methionine and triton methionine group: they were injected with triton (300 ml/kg body weight) and methionine amino acid at (35 mg/kg diet) concentration. Dosing process took place daily for a period of (8) weeks.The study showed a significant decrease at the probability value (P≤0.05) in the concentration of each of cholesterol, triglycerides, LDL-c, VLDL-c, the atherogenic index, and glucose, however, HDL-c levels were found to be higher in this group compared to the control group. Treatment with methionine also led to an improvement in some physiological and biochemical parameters of rats that were subjected to triton stress. Keywords: methionine, triton, lipoproteins, atherogenic index